Radionanotheranostics for breast cancer diagnosis and therapy: recent advances and future opportunities - Mehata A.K.; Viswanadh M.K.; Solomon V.R.; Muthu M.S. (My University, 2025)
Breast cancer is one of the highest causes of mortality in women globally. Poor tumor permeability, multidrug resistance, delayed diagnosis, and complications associated with staging of breast tumor have led to many difficulties in managing this dreadful disease. The advancements in novel techniques in diagnostic and therapeutic applications have conferred nanomedicine as the most promising branch among all biomedical applications. Over the last two decades, radiotherapy’s role in treating cancer patients has grown tremendously. Recently, the world has witnessed enormous development in cancer radiotherapy and its combination with other novel cancer treatment methods like radionanotheranostics, which has provided significant benefits to cancer patients. Radionanotheranostics has revolutionized real opportunities for the evolution of a highly specified therapeutic system with reduced untoward effects. Radiotheranostic nanomedicine aims to design an effective and trustworthy platform for proper cancer treatment and imaging. To achieve this, surface conjugation of targeting ligand, payload of the drug, and radionuclide in single nanomedicine systems have demonstrated an advanced radionanotheranostic approach for breast cancer both in vitro and in vivo. This chapter attempts to systematically review the different types of radionanotheranostics currently under development for breast cancer diagnosis and therapy. © 2022 Elsevier Inc. All rights reserved.